The creativity of Iban sub-ethnic group of Dayak people community in maintaining and preserving customary forests in Sungai Utik Hamlet, Batu Lintang Village, Kapuas Hulu Regency, West Borneo - Bahri, Saiful; Lestari, Emi Tipuk; Nawawi, Nawawi; Paiman, Paiman (Creativity Studies, 2025)
This study aims to analyze the creativity of the Iban sub-ethnic group of Dayak people community in Sungai Utik Hamlet, Batu Lintang Village, Kapuas Hulu Regency, West Borneo, in maintaining and preserving customary forests from the perspective of Earth ethics theory and Weberian social actions. The research model used community-based participatory research which consists of four phases, namely: 1) building basic principles and concepts of the research; 2) research planning; 3) information collection and analysis; and 4) action on findings. The results of the research showed that the community has creativity in managing customary forests, by communities while maintaining integrity, stability, and beauty. The motives for social actions to preserve customary forests were viewed from Max Weber’s theory, namely: 1) traditional actions – communities want to preserve customary forests for generations; 2) effective actions – customary forests were believed to be blood, breath, and considered as the father and mother of the community; 3) instrumental rationality – it can be seen that the central, regional, and traditional heads and Iban sub-ethnic group of Dayak people community strongly support the process of implementing customary forest management traditions; and 4) rationality of values – indigenous peoples had obtained an example of knowledge of integrity, stability, and beauty in customary forest management from their ancestors. Research findings show that the Iban sub-ethnic group of Dayak people community has a genius local concept in customary forest management. Knowledge and values applied in the creativity of customary forest management become an example of life values that are very meaningful and useful for indigenous peoples in understanding forest ecology. Future research still needs to increase creativity in customary forest management.